C5a causes limited, polymorphonuclear cell-independent, mesenteric ischemia/reperfusion-induced injury - Fleming, Sherry D (Clinical immunology (Orlando, Fla.), 2003)
C5 is critical in the development of local mucosal damage and inflammation as well as in the development of remote organ injury after mesenteric ischemia/reperfusion (IR). To define the role of C5a in tissue injury, we treated wild-type mice with a cyclic hexapeptide C5a receptor antagonist (C5aRa) and administered recombinant C5a to C5 deficient (C5(-/-)) mice subjected to mesenteric IR. We demonstrate that at 2-h postreperfusion, C5a administered to C5-/- mice during IR induces limited intestinal mucosal injury but failed to cause remote lung injury despite the fact that it upregulated adhesion molecule expression. C5aRa treatment of C5+/+ mice undergoing IR limited local injury and prevented distant organ injury. We conclude that although C5a can trigger certain components of the IR induced injury, other mediators such as C5b-9 and local factors are needed for the complete expression of IR tissue damage